PENGARUH SUPERVISI DAN TANGGUNG JAWAB TERHADAP PRODUKTIVITAS GURU SMA SWASTA DI WILAYAH JAKARTA SELATAN - Amin Ilyas (Jurnal Manajemen Pendidikan, 2018)
The aim of this research is to investigate the effect of supervision and responsibilty on teacher productivity at private high schools in South Jakarta.The research was conducted using survey method with quantitative approach. The population of this research is 134 teachers from which a research sample of 100 teachers is selected by using simple random sampling technique. The data was obtained through questionnaires and then analyzed using path analysis techniques. Based on the results of data analysis in this research it is conluded that: 1) supervision has a positive direct effect on productivity; 2) responsibility has positive direct effect on productivity; and 3) supervision has positive direct effect on responsibility. Therefore teacher productivity can be improved through improvements in supervision they receive and enhancement in their responsibility.